Peran orang tua dan guru dalam pendidikan Anak zaman sekarang - setyo, jofan amirul (Maliki Interdisciplinary Journal, 2025)
Technological developments and social changes have a major impact on children’s education in modern times. This paper examines the important role of parents and teachers in supporting children’s education in the current era, and how cooperation between them can further improve the effectiveness of learning and character building in children. Social transformation and technological advances have now had a significant impact on children’s education in modern society. In addition, parents and teachers have a vital function in supporting children’s education, both in terms of academics and character building. This paper aims to investigate the tasks of both parties in today’s children’s education, with an emphasis on collaboration between homes and educational institutions. The methodology used in this article is qualitative research using literature studies, with information collection from various books, articles, journals, and online sources. The findings from the discussion of this article indicate that the active involvement of parents and teachers in children’s education can increase learning motivation and the development of children’s character as a whole.